"Three Hits" Hypothesis for Developmental Origins of Health and Diseases in View of Cardiovascular Abnormalities. Issue 10 (16th May 2017) - Li, Xiang; Zhang, Mengshu; Pan, Xinghua; Xu, Zhice; Sun, Miao
Abstract : "Fetal Origins of Adult Diseases" (FOAD) or "Barker hypothesis, " also known as the developmental origins of health and diseases (DoHaD), was initially proposed by David Barker in the 1980s. Progress in past 2 to 3 decades demonstrated that many adult disorders, including hypertension, diabetes, obesity, cancer, and others, could be linked to poor development resulting from in utero insults. Utero‐environments play a critical role in fetal development. Because the placenta and umbilical cord are the only important connections between the fetus and mother in the uterus, this review pays special attention to recent research and progress in the study of the relationship between those tissues and FOAD. We discuss the conception and possible underlying mechanisms of FOAD, and focus on cardiovascular diseases and epigenetic mechanisms. This review also summarizes physiology, pathology, and the important roles of fetoplacental vasculature, which might contribute to FOAD as initiators. We proposed the "Three hits" hypothesis that highlights the importance of intrauterine and early postnatal factors as contributors to FOAD, which could be significant for early prevention and treatments of FOAD. Birth Defects Research 109:744–757, 2017. © 2017 Wiley Periodicals, Inc.